Khyber Pakhtunkhwa food outlook report: Kharif crops 2021-22 - Qureshi, Tehseen Ahmed; Obaid, Rahema; Davies, Stephen; Rana, Abdul Wajid (International Food Policy Research Institute, 2021)
A food outlook report explains the past, current, and future situation of various crops in a specific geographical location. A food outlook report is useful in showing the trends and fluctuations in the cultivated area, production, yield, prices, and other variables. This information is helpful for relevant stakeholders in determining the possible impending shortages or gluts in the food market. A timely analysis on food output and prices can enable policymakers to make wellinformed decisions that can result in controlling market distortions. A major benefit of such reports is that it can predict any anticipated shock or guide about exploiting a growing opportunity. The forecasts conducted in this food outlook report can be helpful in determining the supply and prices of the crops at their harvesting time. To counter a foreseeable shortage or glut, governments can work with the relevant stakeholders to enable timely imports or exports of the crop. One of the main objectives of this paper is to make timely and evidence-based decisions to overcome gaps between food production and consumption growth, and to increase access of the growing population to affordable foods.